Soil Heavy Metal Distribution with Depth around a Closed Landfill and Their Uptake by Datura stramonium - Peace Makuleke; Veronica M. Ngole-Jeme (Applied and Environmental Soil Science)
Landfills are major sources of environmental pollution. This study evaluated heavy metal concentrations in soils and plants around the closed Lumberstewart landfill in Bulawayo, Zimbabwe, to determine the pollution potential of a closed landfill and the risks they present to plants growing in this environment and surrounding communities. Soil samples were collected at depths of 0–30 cm, 30–60 cm, and 60–90 cm around the landfill and at a control site and characterized for various properties and concentrations of Cd, Cu, Cr, Fe, Ni, and Zn. Samples of Datura stramonium, collected from the same sites where soil samples were collected, were also analyzed for the same heavy metals. The soils were sandy, mostly acidic (5.01 < pH < 7.65) with low organic matter content (<2%) and cation exchange capacity (<15 meq/100 g). These properties varied with depth around the landfill. Heavy metals concentrations in the soils and Datura stramonium followed the order Fe > Zn > Cu > Cr > Ni > Cd with samples from around the landfill having higher concentrations than samples from the control site. Soil heavy metal enrichment was highest at a depth of 30–60 cm. Pollution load index (PLI) values indicated that all sites around the landfill were polluted (PLI > 1). Heavy metal transfer coefficient in Datura stramonium ranged between 0.0 and 209 with <60% of the variation observed in heavy metal transfer coefficient in Datura stramonium explained by the extent of heavy metal enrichment in the soils. More than 20 years after closure of the landfill, there are indications that leachate migration may still be going on around the landfill. Monitoring of environments around closed landfills needs to be ongoing to mitigate negative impacts on humans and the environment.